Assessing Russia's decline : trends and implications for the United States and the U.S. Air Force - Oliker, Olga (Rand, 2002)
Continuing trends toward military, political, economic, and social decline in Russia threaten the interests of the United States and its allies. Moscow?s capacity to govern is called into question by increasing crime and corruption (and by political and economic regionalization). Both the military nuclear arsenal and the civilian nuclear power sector present risks of materials theft or diversion, as well as of tragic accident. An increasingly aging and ailing population bodes ill for Russia?s future. Reversing the country?s economic decline and rebuilding an effective military have proven.